# Module 1

```Department of Education
MATHEMATICS 9
First Quarter – Week 1
Writer
DR. FELISA G. BASIJAN, CRISTINE CAROLINE C. GRATIS,
CHARISMA JOY S. LULU, BENELIN G. RUMBAOA
Validators
DR. EMELITA D. BAUTISTA, ENGR. ROLANDO S. MULDONG,
JOSEPH D. NILO, KRYSTELLE R. DUMLAO
Quality Assurance Team Members
Schools Division Office – Muntinlupa City
Student Center for Life Skills Bldg., Centennial Ave., Brgy.Tunasan, Muntinlupa City
(02) 8805-9935 / (02) 8805-9940
This module was designed to give you an opportunity to have a deeper
understanding of quadratic equations. After going through this module, you are
expected to:
Directions: Choose the letter of the correct answer.
1. A mathematical sentence of degree 2 that can be written in the form ax2+bx+c = 0
where a, b, and c are real numbers and a is ≠ 0.
C. linear equation
D. linear inequality
2. Which of the following is a quadratic equation?
A. 2r2 + 4r - 1
C. x2 + 5x - 4 = 0
B. 3t - 7 = 2
D. 2a2 – 7a ≥ c = 0
3. In the quadratic equation 5x2 + 3x = 7, which is the quadratic term?
A. x2
C. 5x2
B. -3x
D. 4
4. What is the value of a in the quadratic equation 9x2 + 4x - 8 = 0?
A. 4
B. 9
C. 0
D. -8
5. A quadratic equation of the form ax2+bx+c = 0 where a, b, and c are real numbers
and a is ≠ 0 is said to be in ______________.
A. slope form
C. slope-intercept form
B. Standard form
D. normal form
6. What is the standard form of 3x + 5x2 = -7
A. 5x2 + 3x = -7
B. 3x + 5x2 + 7 = 0
C. 5x2 + 3x +7 = 0
D. 3x + 5x2 = -7
7. In the quadratic equation ax2 + bx + c = 0, a is ≠ ___.
A. 1
B. 0
C. 2
8. Write the equation (2x + 7) (x - 1) = 0 in the standard form.
A. 2x2 + 9x -7 = 0
C. 2x2 + 5x -7 = 0
B. 2x2 – 9x + 7 = 0
D. 2x2 – 5x + 7 = 0
2
D. −1
9. In the equation 5 - 2x2 = 6x, what is the value of a?
A. 5
B. 6m
C. -2
D. -5
10. Which of these equations describes a quadratic equation?
A.2(x + 3)2 = 0
B. y + 3x2 - 0
C. 3x - 2
D. (x + 3) + 8 = 0
A. Find each indicated product:
1. 3(x2 + 7)
4. (x + 9) (x + 4)
2. 2x (x – 4)
5. (2t – 1) (t + 5)
3. 9(w + 7) (w + 3)
6. (8 – 3x) (8 + 3x)
We start this module by accessing your knowledge of the different mathematics
concepts previously studied and your skills in performing mathematical operations.
go through this lesson, think of this important question: &quot; how are quadratic
equations used in solving real-life problems and in making decisions?&quot; To find the
If a linear equation is of the first degree, then the quadratic equation is of the
second degree. And this is the simplest characteristic that distinguishes one from
the other.
A linear equation is in the form ax + b = 0, where a and b are real numbers and a ≠
0. On the other hand, a quadratic equation takes the form ax&sup2; + bx + c = 0, where
a, b, and c are all real numbers and a ≠ 0. These equations are both in standard
form.
3
Illustrative Example
Determine which of these are quadratic equations.
1. C = 2πr
3. x + 3x = 0
5. x&sup2; - 2x + 1 = 0
2. 2x&sup2; - 5x + 1 = 0
4. 3x&sup2; - 5 = 0
6. A = πr&sup2;
Solution:
Equations 2, 4, 5, and 6 are quadratic equations.
A quadratic equation in one variable is a mathematical sentence of degree
two that can be written in the following standard form, ax&sup2; + bx + c = 0, where a, b,
and c are real numbers and a ≠ 0. In the equation, ax&sup2; is the quadratic term, bx is
the linear term, and c is the constant term.
Example 1: 3a&sup2; + 2a - 4 = 0 is a quadratic equation in the standard form with a =
3, b = 2 and c = -4.
Example 2: 4x (x - 3) = 5 is a quadratic equation. However, it is not written in
standard form. To write the equation in standard form, expand the product and
make one side of the equation zero as shown below
4x (x - 3) = 5
4x&sup2;- 12x = 5
4x&sup2;- 12x - 5 = 5 - 5
4x&sup2; - 12x – 5 = 0
The equation becomes 4x&sup2; - 12x – 5 = 0, which is in the standard form. In the
equation 4x&sup2; - 12x – 5 = 0, a = 4, b = -12 and c = -5
Example 3: The equation (2x + 5) (x - 1) = -6 is also a quadratic equation but it is
not written in standard form same with example 2. The equation (2x + 5) (x - 1) = -6
can be written in standard form by expanding the product in making one side of
the equation equal to zero as shown below
(2x + 5) (x - 1) = -6
2x&sup2;- 2x + 5x -5 = -6
2x&sup2; + 3x -5 = -6
2x&sup2; + 3x -5 + 6 = -6 + 6
2x&sup2; + 3x + 1 = 0
The equation becomes to 2x&sup2; + 3x + 1 = 0, which is in standard form. In the
equation 2x&sup2; + 3x + 1 = 0, a = 2, b = 3, and c = 1.
When b = 0, in the equation ax&sup2; + bx + c = 0, it results to a quadratic equation
of the form ax&sup2; + c = 0.
Examples: Equation such as x&sup2; + 5 = 0, 2x&sup2; + 7 = 0, and 16x&sup2; - 9 = 0 are
quadratic equations of the form ax&sup2; + c = 0. In each equation, the value of b = 0.
4
Directions: Identify which of the following equations are quadratic and which are
not.
1) x (x2 + 3) = 8
2) x2 – 1 = 0
3) x2 = 16
4) (4 - x)2 = 3x
5) (x2 + 2)2 – 5 = 0
6) (2x - 5) + 2 = 0
7) 3x2 – 10 = 4x
8) (x - 5)2 = 2
9) 2 (x + 3)2 = 0
10) (x - 1)2 + 6 = 0
11) x(x + 3)2 = 7
12) 4 = 2 (x + 1)2
13) 5 (3x + 2) = 4
14)
3x2 + 1
x
15)
x2 + 3
5
= x2
=0
Activity 2. Set Me to Your Standard
Write each quadratic equation in standard form, ax&sup2; + bx + c = 0, then identify
the values of a, b, and c.
1. 3x + 2x&sup2; = 7
2. 5 + 2x&sup2; = 6x
5
3. (x + 3) (x + 4) = 0
4. (2x + 7) (x - 1) =0
5. 2x (x - 3) = 15
A quadratic equation in one variable is a mathematical sentence of degree two
that can be written in the following standard form, ax&sup2; + bx + c = 0. Where a, b,
and c are real numbers and a ≠ 0. In the equation, ax&sup2; is the quadratic term, bx is
the linear term, and c is the constant term.
I. Put a check on the blank if the equation is quadratic or not.
1) 5 (x - 7) = 0
2) 15 = x2
3) (x + 2)2 = x2
4) 3x (x + 2)2 = 5
5) x (2x + 5)2 = 0
6) x [(2 + x)2] = 0
7) 2 [(4x - 1)2] = 8
8) x (x + 3) = 6
9) 5 (x - 5) = 2
10) x (3x2 – 2x + 1) = 0
6
II. Write each equation in the form of ax2 + bx + c = 0 and identify the value of a, b,
and c.
Equation
In the form of ax2 + bx + c
=0
Values of
a
b
c
1) 2x2 - 6x = 3x
2) 2 (3x + 1)2 = 0
3) 5 = (4x + 1)2 + 6
4) 7 (2x2 - 1) = 5x
5) 2 (3x + 5) = x2
6) 2x (3x - 3) + 7 = 0
7) 3 (x – 2)2 = 6
8) 2x – 3 = 2(x – 1)2
9) 3x + 5 = 4(x + 1)2
10) 7x + 1 = (2x - 1)2
11) 2x2 = (x + 3)2
12) 8x = 4(x2 + 2x)
13) 6 = (3x + 1)2
14) (3x + 1)2 = 4(x –
1)2
15) 8x2 + 3 = - 4x
Directions: Choose the letter of the correct answer.
1. Which of this equation describes a quadratic equation?
A. 2(x + 3)2 = 0
B. y + 3x2 = 0
C. 3x – 2 = 0
D. (x + 3) + 8 = 0
2. In the equation 5 - 3x2 = 6x, what is the value of c?
A. 5
B. 6
C. -2
7
D. -5
3. Write the equation (2x + 7) (x + 1) = 0 In the standard form.
A. 2x2 + 9x – 7 = 0
C. 2x2 + 5x – 7 = 0
B. B. 2x2 + 9x + 7 = 0
D. 2x2 - 5x + 7 = 0
4. In the quadratic equation ax2 + bx + c = 0, a ≠ _.
A. 1
B. 0
C. 2
D. -1
5. What is the standard form of 3x + 5x2 = -7
A. 5x2 + 3x = -7
C. 5x2 + 3x +7 = 0
B. 3x + 5x2 + 7 = 0
D. 3x + 5x2 = -7
6. A quadratic equation in the form of ax2 + bx + c = 0 where a, b, and c are all real
numbers and a ≠ 0 is said to be in _____________.
C. factoring
B. standard form
7. In the quadratic equation 9x2 + 8x - 8 = 0, what is the value of a?
A. 4
B. 9
C. 0
D. −8
8. Which is the quadratic term in the quadratic equation 5x2 - 3x + 4 = 0?
A. x2
B. – 3x
C. 5x2
D. 4
9. Which of the following is a quadratic equation?
A. 2r2 + 4r – 1
C. x2 + 5x - 4 = 0
B. 3t - 7 = 2
D. 2a2 – 7a ≥ c = 0
10. A mathematical sentence of degree 2 that can be written in the form ax2+bx+c =
0 where a, b, and c are real numbers and a is ≠ 0.
C. Linear equation
D. Linear inequality
8
Pretest
Activity 1
1. A
2. C
Post Test
Check
Your
Understan
ding
3. C
I.
3. B
4. B
1.
4. B
5. B
2. ✓
5. C
6. C
3.
6. B
7. B
4.
7. B
8. C
5.
8. C
9. C
6.
9. C
10. A
7. ✓
10. A
8. ✓
9. ✓
10.
Activity 2
1) 2x2 + 3x – 7 = 0; a= 2, b = 3,
c = -7
2) 2x2 – 6x + 5 = 0; a = 2, b = 6, c = 5
3) x2 + 7x + 12 = 0; a = 1, b =
7, c = 12
4) 2x2 + 5x – 7 = 0; a = 2
5) 2x2 – 6x – 15 = 0; a = 2, b = -6, c = 15
9
1. A
2. A
II.
Equation
1) 2x2 - 6 = 3x
2) 2 (3x + 1)2 = 0
Values of
In the form of ax2 +
bx + c = 0
a
b
c
2x2 – 3x – 6 = 0
2
-3
-6
18
12
2
18x2 + 12x + 2= 0
3) 5 = (4x + 1)2 + 6
16x2 + 8x + 2 = 0
16
8
2
4) 7 (2x2 - 1) = 5x
14x2 – 5x – 7 = 0
14
-5
-7
5) 2 (3x + 5) = x2
x2 – 6x – 10 = 0
1
-6
-10
6) 2x (3x - 3) + 7 = 0
6x2 – 6x + 7 = 0
6
-6
7
7) 3 (x – 2)2 = 6
3x2 – 12x + 6 = 0
3
-12
6
8) 2x – 3 = 2(x – 1)2
2x2 – 6x + 5 = 0
2
-6
5
9) 3x + 5 = 4(x + 1)2
4x2 + 5x – 1 = 0
4
5
-1
10) 7x + 1 = (2x - 1)2
4x2 – 11x = 0
4
-11
0
11) 2x2 = (x + 3)2
X2 - 6x – 9 = 0
1
-6
-9
4x2 = 0
4
0
0
13) 6 = (3x + 1)2
9x2 + 6x – 5 = 0
9
6
-5
14) (3x + 1)2 = 4(x – 1)2
5x2 + 14x - 3 = 0
5
14
-3
15) 8x2 + 3 = - 4x
8x2 + 4x + 3 = 0
8
4
3
12) 8x = 4(x2 + 2x)
References
Learner’s Material for Mathematics -Grade 9, pages 11 - 17
E-MATH (Worktext in Mathematics 9), page 82
10
```